PERLINDUNGAN HUKUM TERHADAP USAHA MIKRO, KECIL MENENGAH (UMKM) DI KOTA PEKANBARU DALAM MENGHADAPI MASYARAKAT EKONOMI ASEN (MEA) - Rani, Nabella Puspa (Jurnal Yuridis, 2015)
When the ASEAN economy opens, the flow of trade in goods and services, investment and labor migration among ASEAN countries are no longer being obstacles. This will provide an opportunity and a challenge for the economic development of all countries that are involved, including Indonesia. Sustainment and competitiveness of UMKM in Indonesia are priorities in the implementation of MEA 2015. This is because UMKM is one of the central points of unemployment and poverty alleviation as well country's economy. UMKM sustains economic system of a particular area of the city specifically Pekanbaru. Based on this phenomenon, it is expected that the government plan efforts and strategies to provide protection for UMKM, particularly legal protection. The aim is to provide a sense of security, both in mind and physical from harassment and various threats to UMKM stakeholders in Pekanbaru to face MEA 2015.